Visual feedback explains why propointing is better than antipointing in spatial neglect. (January 2018) - Utz, Kathrin S.; Hesse, Constanze; Hintz, Annika; Grüneberger, Daniela; Kulke, Hartwig; Roth, Inga; Klos, Thomas; Kromichal, Vaclav; Melms, Arthur; Schupp, Wilfried; Kohl, Detlef; Schenk, Thomas
Abstract: Rossit et al. (2011) showed that neglect patients perform normally in a propointing task but not in an antipointing task which requires pointing towards the mirrored position of a target. It is assumed that antipointing relies on information from the perceptual pathway of our visual brain. Therefore, this finding supports the notion that neglect is a disorder that primarily affects perceptual spatial representations within the brain leaving spatial maps used for visuomotor guidance intact. Alternatively, performance of patients might be compromised in both tasks, but only obviously so in tasks in which online corrections are made more difficult. It can be argued that online-corrections via visual feedback are less effective in antipointing because a direct comparison between hand and target is not possible in this condition. Secondly, it is also known that neglect patients have a pronounced egocentric bias which is assumed to be associated with a deviation of the perceived body midline. Since the midline is used to compute the end-position in the antipointing task this could also explain why patients are worse in antipointing. We investigated the influence of visual feedback on pro- and antipointing and the effect of providing a visual reference line for the antipointing task in right-brain damaged patients with neglect (n = 20), right-brain damaged patients without neglect (n = 23) and in a group of healthy participants (n = 22). The withdrawal of visual feedback had a stronger effect on propointing compared to antipointing. This effect was stronger in neglect patients than in patients without neglect or healthy controls. The introduction of a reference line reduced errors in antipointing performance, particularly in neglect patients with a strong egocentric bias. The results support our alternative account and challenge the hypothesis that the spatial disorder in neglect affects primarily perceptual maps within the visual system.